2016
DOI: 10.5380/rf.v46i3.42931
|View full text |Cite
|
Sign up to set email alerts
|

ASPECTOS ECONÔMICOS DOS PLANTIOS COM EUCALIPTO (Eucalyptus spp.) NA REGIÃO DO BAIXO ACRE

Abstract: ResumoO objetivo desse artigo foi, ao gerar informações econômicas sobre a atividade de reflorestamento com Eucalyptus spp., no estado do Acre, subsidiar a formulação de políticas públicas voltadas à utilização dos recursos florestais locais. Em termos específicos, essa pesquisa visou: (a) identificar os custos relacionados à implantação e manutenção de povoamentos de eucalipto na região do Baixo Acre; (b) quantificar as receitas da atividade de reflorestamento nessa região; e (c) avaliar a viabilidade econômi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…The implantation cost found in the present study was $884.18 ha -1 and the wood sale by $13.51 m³ made the project viable, with NPV of $40.26 ha -1 and EPV of $16.80 ha -1 . In another study, Eucalypt production was economically unfeasible, with and without land cost consideration, with NPV of -$865.92 ha -1 and -$1,182.92 ha -1 , respectively, at an interest rate of 6% year (Queiroz and Silva, 2016). The authors found that the implantation cost ($1,077.13 ha -1 ) and wood standing sale revenue ($808.92 ha -1 ), marketed to $2.84 m³ , were not suffi cient to off set the negative cash fl ow.…”
Section: Discusionsmentioning
confidence: 99%
“…The implantation cost found in the present study was $884.18 ha -1 and the wood sale by $13.51 m³ made the project viable, with NPV of $40.26 ha -1 and EPV of $16.80 ha -1 . In another study, Eucalypt production was economically unfeasible, with and without land cost consideration, with NPV of -$865.92 ha -1 and -$1,182.92 ha -1 , respectively, at an interest rate of 6% year (Queiroz and Silva, 2016). The authors found that the implantation cost ($1,077.13 ha -1 ) and wood standing sale revenue ($808.92 ha -1 ), marketed to $2.84 m³ , were not suffi cient to off set the negative cash fl ow.…”
Section: Discusionsmentioning
confidence: 99%
“…Em estudo realizado por Queiroz, Silva (2016), ao avaliar os aspectos econômicos de um povoamento de Eucalyptus spp. para lenha na região do baixo Acre, considerando a venda da madeira com e sem o custo da terra, foram encontrados VPL's negativos utilizando diferentes TMA's (6%, 8%, 10% e 12%), apontando a inviabilidade da atividade para a região em questão, devido ao alto custo de produção ou até mesmo do baixo valor de mercado para comercialização da lenha.…”
Section: Atividadeunclassified
“…An example of this is that in Brazil, in 2014, herbicide use totaled 476,860 tons, representing more than half of the amount of plant protection products marketed that year, reaching US$ 3.90 billion (Ferreira & Vegro, 2015). In the management of eucalyptus plantations, weed control is a factor of considerable relevance for wood productivity and final net income, representing around 20-25% of the total cost in a 7-year cycle (Rodigheri, Pinto, & Dhlson, 2001;Queiroz & Silva, 2016).…”
Section: Introductionmentioning
confidence: 99%